Corporate Social Responsbility Sebagai Pemoderasi Pengaruh Komponen Good Corporate Governance Terhadap Profitabilitas - Putra, Made Kusuma Rahardi; Alit Suardana, I Ketut (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
The purpose of this study was to determine the effect of the component of good corporate governance on profitability by moderating corporate social responsibility. The location of this research is the State-Owned Enterprises (BUMN) which are listed on the Indonesia Stock Exchange during the period 2013-2015. The number of observation samples over a period of 5 years is 50 with the sampling method used is non probability sampling with a purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the study shows that institutional ownership and independent board of commissioners have a positive and significant effect on profitability while the audit committee has no effect on profitability. The moderating corporate social responsibility variable weakens the relationship of institutional ownership to profitability, and corporate social responsibility is not a moderating variable on the relationship between independent commissioners and audit committees on profitability. Keywords: Good corporate governance, corporate social responsiveness, profitability